THE RELATIONSHIP BETWEEN ADVERSITY QUOTIENT AND ACADEMIC PROCRASTINATION AMONG STUDENTS OF SMPN 23 MEDAN - Miranda Febryolita Situmorang; Asina Christina Rosito; Nancy Naomi G.P . Aritonang (Yayasan Nuraini Ibrahim Mandiri, 2026)
Academic procrastination is a tendency for students to delay completing academic tasks which can have an impact on declining learning achievement. This behavior is often found in students in formal educational settings, including at the Junior High School level. One of the psychological factors that is suspected to be related to this behavior is the adversity quotient, which is the individual's ability to face and overcome difficulties. Students who have a high adversity quotient tend to have better fighting power in facing academic challenges so that they are able to reduce academic procrastination behavior. This study aims to determine the relationship between adversity quotient and academic procrastination in students of SMPN 23 Medan. This study uses a quantitative approach with a correlational method. The study population was 1052 students, with a sample of 285 students selected from several classes. Data collection was carried out using a Likert scale instrument in the form of a closed questionnaire. Data analysis used the Spearman Rank correlation test which was preceded by the normality test and the linearity test. The results of the study show that there is a strong and significant relationship between adversity quotient and academic procrastination with the direction of negative relationships. This shows that the lower the adversity quotient of students, the higher the tendency of academic procrastination